Jurisdiction of International Court of Justice (ICJ) Over the Genocide Violations: with Special References to Rohingya Case - Yordan Gunawan; Sonya Whisler Refisyanti; Aliza Mufida; Kukuh Derajat Takarub; Aisah Nur (Universitas Lampung, 2020)
In 2019, Gambia, a small country which located in West Africa, is suing Myanmar to the International Court of Justice (ICJ) with alleging that Myanmar has violated the Convention on the Prevention and Punishment of the Crime of Genocide 1948. The governments of Myanmar in doing the violations were intended to destroy the Rohingya Muslim as a group, wholly or partly, followed by other violations such as mass murder, rape, and also damage to the villages by fire with some people are still locked in the house and burnt inside the house. Government of Myanmar keep doing so, because based on Burma Citizenship Law 1982, Myanmar doesn’t recognize the existence of Rohingya as citizen of Myanmar. It causes Rohingya as stateless. The study is normative legal research with Statute Approach and Case Approach. The study analyse the violations which is done by Myanmar to the Rohingya Ethnic in Rakhine. The result shows that International Court of Justice has a jurisdiction upon Rohingya case under the Statute of the Court as well as the Genocide Convention. The statute of the Court in Article 36 (1) stated that ICJ has jurisdiction to all cases of the Convention as long as the states are contracting parties. The Article IX of the Convention also stated that any dispute between contracting parties must be referred to ICJ.